Procons omega-3: the key to fighting inflammation and preventing muscle loss in sarcopenic patients - Tjakradidjaja, Francisca A (Jurnal Konseling dan Pendidikan, 2025)
Sarcopenia, an age-related progressive loss of muscle mass and function, is a significant public health concern that increases the risk of frailty, falls, and disability among older adults. Inflammation plays a crucial role in accelerating muscle degradation, making anti-inflammatory interventions essential in managing sarcopenia. This study employs a qualitative approach through literature review and library research to explore the potential of omega-3 fatty acids as a therapeutic strategy for preventing muscle loss and mitigating inflammation in sarcopenic patients. Omega-3 polyunsaturated fatty acids (PUFAs), particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), exhibit potent anti-inflammatory properties that regulate cytokine production and muscle protein synthesis pathways. Existing studies indicate that omega-3 supplementation can enhance muscle protein anabolism, reduce systemic inflammation, and improve physical function in older adults at risk of sarcopenia. Moreover, omega-3 fatty acids modulate key inflammatory markers such as tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6), which are linked to muscle degradation. Through an in-depth analysis of scientific literature, this study highlights the potential benefits of omega-3 supplementation as a non-pharmacological intervention for sarcopenia. However, further clinical trials are needed to determine the optimal dosage, duration, and long-term effects of omega-3 on muscle preservation. The findings of this study contribute to the growing body of research advocating for dietary interventions as a preventive strategy against age-related muscle loss and chronic inflammation.